Shear bond strength between dental adhesive systems and an experimental niobium-based implant material - N. Brümmer; C. Klose; J-T. Schleich; H. J. Maier; M. Eisenburger; M. Stiesch; P.-C. Pott (Journal of Materials Science: Materials in Medicine)
Abstract This study aimed to investigate adhesive shear bond strength (SBS) on an ultrafine-grained niobium alloy (UFG-Nb) that is a potential dental implant material. SBS of three adhesive systems combined with three composites to UFG-Nb was compared to corresponding SBS to Ti-6Al-4V and to zirconia. Specimens of the substrates UFG-Nb, Ti-6Al-4V and zirconia with plane surfaces were sandblasted with Al2O3, cleaned and dried. Three adhesive systems (Futurabond U, Futurabond M + , Futurabond M + DCA; all VOCO GmbH, Cuxhaven, Germany) were applied each on specimens of each substrate and light cured. One composite (BifixSE, BifixQM, GrandioSO; all VOCO GmbH) was applied and light cured resulting in 27 groups (n = 10) for all substrate-adhesive-composite-combinations. SBS was measured after 24 h of storage. To simulate aging equally prepared specimens underwent 5000 thermocycles before SBS measurement. There was no significant difference in SBS within the non-aged groups. Among the artificially aged groups, GrandioSO-groups showed a greater variance of SBS than the other composites. All significant differences of corresponding UFG-Nb-, Ti-6Al-4V- and zirconia-groups with same adhesive-composite-combination (ACC) were observed between UFG-Nb and zirconia or Ti-6Al-4V and zirconia but never between the two metallic substrates. The similarity between these materials might show in their adhesive bonding behavior. As there were no differences comparing corresponding groups prior to and after artificial aging, it can be concluded that aging does not affect SBS to UFG-Nb, Ti-6Al-4V and zirconia using the tested ACCs. Adhesive bonding of established ACCs to UFG-Nb is possible resulting in SBS comparable to those on Ti-6Al-4V and zirconia surfaces. Graphical Abstract